Joint resource allocation algorithm based on throughput maximization in D2D communication - Yue Qiu; Yinghe Wang; Chong Tan; Min Zheng; Yu, Kai (2015 4th International Conference on Computer Science and Network Technology (ICCSNT), 2015)
Specific to the maximization of the system throughput, the joint resource allocation schemes for Device-to-Device (D2D) communication are proposed. Another purpose of the joint resource allocation schemes is to avoid the strong interference between cellular communication and the D2D communication. The core strategy of the algorithm is to establish a throughput matrix and find maximum throughput according to the D2D and cellular users. The results show that the proposed methods significantly improve the system throughput and the number of permitted D2D users. The performance of the proposed scheme for jointly allocation scenario is preferable to that of the proposed scheme for independently allocation scenario in some ways. The algorithm has four steps to solve problem of channel resource shortage: divided multiplexing channel selection, D2D communication access, potential channel selection and resources allocation. In order to avoid the high complexity of the exhaustive search for optimal resource allocation algorithm, we have achieved a good balance between performance and efficiency.